Harmonic analysis of nonlinear loads using filter / Mohd Fahmi Abdul Halim - Abdul Halim, Mohd Fahmi (2010)
Power quality is the degree to which both the utilization and delivery of electrical power affect the performance of electrical equipment. Harmonics power quality issues have been taken into consideration. Harmonics is a term that describes sinusoidal waveforms that operate at a frequency that is a multiple of the fundamental 50Hz frequency in Malaysia. Harmonic in power systems shortens the equipment's life expectancy and effect in the electrical distribution system. The most significant effects of high frequency harmonic current such as inductive heating of transformers, generators, motors, relays and coils. This paper presents the modeling of nonlinear electrical loads used in domestic and small scale industrial distribution systems to estimate the harmonic distortion. In this paper, personal computer and fluorescent lamp are developed as simulation models for nonlinear loads. Analysis of current harmonics is performed for these loads individually by simulation software using MATLAB-SIMULINK. Total Harmonics Distortion (THD) is used as the harmonic index to study the effect of these nonlinear loads at the utility. In order to eliminate these harmful harmonics and improve system reliability, passive filter located at the line supply of these models. Simulations are carried out with and without the filters to analyse the harmonics on the nonlinear loads. The current waveforms, frequency spectrum and dominant harmonics in each model are recorded.